ASSESSING THE ROLE OF THE ISLAMIC REPUBLIC OF IRAN IN THE EU ENERGY MARKET - Alireza Koohkan, Mohammad Ardam, Ellias Aghili Dehnavi, Mohammad Ghanbari Barzyan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
EU countries are among the poorest countries in the world in terms of energy resources, while energy is a vital vessel in the EU's economy, and the continued growth of people's welfare and livelihoods, as well as the strength of their industry, depends on energy resources. The bitter experience of the 1973 oil embargo and the Russian gas cut in 2009 prompted Europeans to seek diversification in their energy markets. In this regard, Iran has attracted the attention of the European Union with its vast resources of oil and gas. The EU is working to help Iran share its energy market. Using a descriptive-analytical method, this study seeks to answer the question of what role can the Islamic Republic of Iran play in the current EU energy market by examining the economic capacities and capabilities of Iran's energy market as well as the EU's energy market capacities. Our hypothesis is that, Since the EU's Green Document shows that the use of fossil fuels in the European Union is on the rise, Iran can meet the energy needs of the European economy due to its unique capabilities.